2022
DOI: 10.1371/journal.pone.0265282
|View full text |Cite
|
Sign up to set email alerts
|

Psychosomatic syndromes are associated with IL-6 pro-inflammatory cytokine in heart failure patients

Abstract: Psychosomatic syndromes have emerged as an important source of comorbidity in cardiac patients and have been associated with increased risk for adverse outcomes in patients with heart failure (HF). Understanding of the mechanisms underlying this connection is limited, however immune activity represents a possible pathway. While there have been numerous studies connecting immune activity to psychosomatic psychopathology, there is a lack of research on patients with HF. We examined forty-one consecutive outpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
0
3
0
1
Order By: Relevance
“…Consistent with the literature (Irwin, 2011; Kiecolt‐Glaser et al, 2005; Takahashi et al, 2018), the current study revealed that more stressors and hurt feelings predicted more SOMA and worse general health. Neuroimmunological studies reveal that stressors increase the level of proinflammatory cytokines, which are associated with nonspecific sickness symptoms (Altamura et al, 2022; Schwarz, 2003). As a result, these detrimental effects may embody more SOMA and worse physical health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the literature (Irwin, 2011; Kiecolt‐Glaser et al, 2005; Takahashi et al, 2018), the current study revealed that more stressors and hurt feelings predicted more SOMA and worse general health. Neuroimmunological studies reveal that stressors increase the level of proinflammatory cytokines, which are associated with nonspecific sickness symptoms (Altamura et al, 2022; Schwarz, 2003). As a result, these detrimental effects may embody more SOMA and worse physical health.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimmunology research shows that dysregulated immune systems underly the association between social stress and aggression (Takahashi et al, 2018). Stressors are associated with inflammatory cytokines, which may lead to sickness behaviors (e.g., fever, anorexia, hyperalgesia, weakness) (Altamura et al, 2022; Irwin, 2011; Schwarz, 2003). Stressful events trigger the state of anger and increase the level of cytokines (Kiecolt‐Glaser et al, 2005; Pesce et al, 2013).…”
Section: Daily Life and Somamentioning
confidence: 99%
“…This study also showed that genipin could regulate the COX2-PGD2 pathway to inhibit the structure-function remodeling in response to MI. Interleukin 6 and TNF-α were serum inflammatory markers, associated with HF and used for clinical evaluation of HF (32,33). The inflammatory markers activated the AA metabolism pathways to accelerate HF development (34).…”
Section: Discussionmentioning
confidence: 99%
“…Как известно, вирусные инфекции, воспаление и эндотелиальная дисфункция участвуют в атерогенезе. Присутствие пожизненных латентных вирусов герпеса в атеросклеротических бляшках может оказывать патогенетическое действие, проникая через артериальную стенку, модифицируя липидный обмен и стимулируя выработку провоспалительных цитокинов и факторов роста [6]. Кумулятивная подверженность множественным инфекционным патогенам, известная как патогенная нагрузка, связана с повышением риска ИБС, воспаления и эндотелиальной дисфункции.…”
Section: ключевые моменты Key Messagesunclassified